Ocenění společnosti Octopus Energy. (Valuation of Octopus Energy) - Kopaleishvili, Irakli; Ali, Tanweer; Kupec, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis aims to assess the valuation and strategic positioning of Octopus Energy Limited, a key participant in the UK's energy market. The research integrates strategic analysis alongside two-stage discounted cash flow valuation to find the intrinsic value as well as identify the firm's strengths, challenges, and long-term potential within the UK's regulatory and market environment. Conclusions will offer insights into the company's operational structure, scalability, and strategic readiness for future growth.
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses